Gaming industry in Singapore. - Chua, Stanley Wee Loon. (2008)
In this research, we look at the different aspects of gambling, namely psychological, social and economic. After which we look at the present gambling scene in Singapore. A survey was conducted to find out the feasibility of introducing new forms of legalised gaming alternatives in Singapore.